The rediscovery of the holotype of Kotonisia kanoi Matsumura, 1938 with notes on Matsumura’s type specimens of Fulgoroidea (Insecta: Hemiptera: Fulgoromorpha) - Tsaur, Shun-Chern (Zootaxa, 2009)
Shonen Matsumura (1872–1960), the founder of entomology in Japan, is no doubt among the most influential and prolific entomologists. He produced a series of works, illustrated lists of the insects and described as many as 1200 new species. Unfortunately, most of the types he named and collected from Taiwan were brought to Japan in the late 1940s, and were hard to access by foreign students until relatively recently.Matsumura’s type depositions contain brief descriptions and, sometimes, only female specimens were available for his types. This prevented sound revisionary work in Taiwan. In addition, Matsumura did not designate holotypes in his early works but simply indicated how many specimens he had.